Repurposing of dexpramipexole to treatment of neonatal hypoxic/ischemic encephalopathy. (20th November 2018) - Muzzi, Mirko; Buonvicino, Daniela; Urru, Matteo; Tofani, Lorenzo; Chiarugi, Alberto
Highlights: dMCAoH was developed as a new model of HIE with a low intra-experimental variability. Post-ischemic treatment with DEX was neuroprotective in rat pups subjected to dMCAoH. DEX reduced injuries in pups subjected to CCAoH showing mild/moderate infarcts. Abstract: Dexpramipexole (DEX) is a drug with a good safety profile in humans, known for its ability to increase mitochondrial ATP production and prompt neuroprotection in adult rodents subjected to cerebral ischemia. In the present study we evaluated the effect of DEX in rat pups subjected to common carotid artery occlusion plus hypoxia (CCAoH, the classic Rice-Vannucci model). Because of the wide range of infarct size distribution in the CCAoH model, a priori subanalysis based on the effect of DEX on mild/moderate or severe brain injuries was conducted. The subanalysis showed that the drug (3 mg/kg bid i.p, after the hypoxic insult) decreased the infarction size in pups with mild/moderate injuries. Next, we developed a distal middle cerebral artery occlusion plus hypoxia (dMCAoH) model, characterized by an intra-experimental infarct size variability lower than that of the CCAoH model. Post-ischemic treatment with DEX (3 mg/kg bid i.p, after the hypoxic insult) reduced brain infarcts in pups exposed to dMCAoH. For the first time, we show that DEX reduces brain injury in different models of neonatal HIE. In light of the favorable safety profile of DEX in humans, the drug might have a realistic translational potential to treatment of perinatal cerebrovascular disorders.